Mycoviruses confer hypovirulence but enhance antifungal volatile organic compound production in a phytopathogenic fungus - Zhijun Liu; Qiangqiang Pan; Huang Huang; Lixia Gao; Zhi Zhou; Dan Zheng; Xueqiong Xiao; Yanping Fu; Jiasen Cheng; Qing Cai; Bo Li; Tao Chen; et al. (Proceedings of the National Academy of Sciences, 2026)
Hypovirulence-associated mycoviruses can be frequently isolated in nature despite their likely compromised ecological fitness, but how their fungal hosts survive in natural environments remains largely unresolved. The discovery of more mycoviruses provides opportunities to understand these mycovirus–host relationships. Here, we characterize a capsidless RNA virus, Sclerotinia sclerotiorum ascoshuvirus 1 (SsAShV1), with a 10.7-kb ssRNA genome encoding a polyprotein containing conserved protease domain and RNA-dependent RNA polymerase (RdRP) domain. SsAShV1 shares structural similarities with animal-infecting viruses. SsAShV1 and its phylogenetically related shuviruses form a distinct evolutionary lineage, prompting the proposal to establish the family Shuviridae. SsAShV1 transfection alone induces hypovirulence in two Sclerotiniaceae fungal pathogens, with its 3’-UTR repeat-containing structural region (RCSR) enhancing replication efficiency. In the hypovirulent strain SCH767, which harbors SsAShV1 and five other mycoviruses, we observed a synergistic enhancement of antifungal volatile organic compound (VOC) production that was dependent on the host genetic background. A VOC, 2-ethyl-1-hexanol, exhibited broad-spectrum antimicrobial activity. Our findings reveal an evolutionary trade-off where viral infection shifts the fungal survival strategy from high virulence to enhanced chemical competition, ensuring the persistence of the hypovirulent partnership, and offering valuable insights into the development of a combination of mycovirus-based and VOC-mediated biocontrol strategies.